The Establishment of Rural Tourism Based Creative Economy Kendran Village, Gianyar - Arismayanti, Ni Ketut; Widyatmaja, I Gusti Ngurah; Wiraatmaja, I Wayan (Udayana Journal of Social Sciences and Humanities; Vol 1 No 1 (2017): UJoSSH, Feburary 2017DO - 10.24843/UJoSSH.2017.v01.i01.p02, 2017)
The aim of the research is to find the identification of the potential of nature tourism, cultural tourism, and creativity of local communities of Kendran Village and determine the condition of the internal environment (as seen from the strengths and weaknesses) and external environment (as seen from the opportunities and threats) of Kendran Village. Since the development of creative economy based rural tourism is one of the attempts to open up the market share (market niche) that had not done yet.SWOT analysis method used in this research to explore the potential of the internal environment, such as Strengths, namely rice field scenery with jogging tracks, the preserved traditional culture as traditional Balinese architecture, sacred places, historical relics in the village area, the activities of the Balinese-Hinduism ceremonies, arts and cultures, as well as the hospitality of communities, and accessible areas. We found the Weaknesses on infrastructure, public facilities, lack of tourism programs along with its management, and lack of foreign languages including English. Likewise, on the external environment, they have the opportunities in location of Kendran Village, the popularity of rural tourism, increasing of tourists arrival who interested in culture & nature tourism, information and technological advances that supports the promotion of Kendran Village, the support of the Gianyar Government, the development of creative economy based tourism, and the Threats such as increased competition in tourism industry, lack of passion of rural life in young generations, the culture commercialization, and also the stability of political and security situation in Indonesia.